Evaluating Access to Eye Care in the Contiguous United States by Calculated Driving Time in the United States Medicare Population - Lee, Cecilia S. (Ophthalmology, 2016)
PURPOSE: To quantify the proximity to eye care in the contiguous United States by calculating driving routes and driving time using a census-based approach. DESIGN: Cross-sectional study based on United States (US) census data, Medicare payment data, and OpenStreetMap. PARTICIPANTS: 2010 US census survey respondents older than 65 years. METHODS: For each state in the United States, the addresses of all practicing ophthalmologists and optometrists were obtained from the 2012 Medicare Provider Utilization and Payment Data from the Centers for Medicare and Medicaid Services (CMS). The US census data from 2010 then were used to calculate the geo-location of the US population at the block group level and the number of people older than 65 years in each location. Geometries and driving speed limits of every road, street, and highway in the United States from the OpenStreetMap project were used to calculate the exact driving distance and driving time to the nearest eye care provider. MAIN OUTCOME MEASURES: Driving time and driving distance to the nearest optometrist and ophthalmologist per state. RESULTS: Driving times for 3.79×10(7) persons were calculated using a total of 3.88×10(7) available roads for the 25 508 optometrists and 17 071 ophthalmologists registered with the CMS. Nationally, the median driving times to the nearest optometrist and ophthalmologist were 2.91 and 4.52 minutes, respectively. Ninety percent of the population lives within a 13.66- and 25.21-minute drive, respectively, to the nearest optometrist and ophthalmologist. CONCLUSIONS: While there are regional variations, overall more than 90% of the US Medicare beneficiary population lives within a 30-minute drive of an ophthalmologist and within 15 minutes of an optometrist.